(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This paper proposes reflections in the field of considering the existence of pluralism as an essential condition for establishing effective democracy and consolidating citizenship. The purpose of this research is the following question: the extent to which pluralism is a tangible institute recognized by law and constitutional hermeneutics, with repercussions on constitutional interpretation and gaining space in the consolidation of the Democratic State or if it is just a dead letter, consisting of mere terminological allegory , that is, without any employability or practical utility? In this study, we strive to walk the paths towards the recognition and understanding of pluralism as a conceptual institute for understanding the role of the Constitution - and its interpretation - as a legitimate political charter. It is based on studies related to constitutional interpretation, pursuing, in this research, the observation of the reflexes of constitutional expressions as guiding for the realization of the constitutional state of right to be built, in which citizenship is valued and, consequently, the realization of the constitutional proposal as an order promoting fundamental rights, based especially on equality - in its most noble sense. It takes as a reference the work of constitutional hermeneutics - Peter Häberle, as well as productions about Derrida’s philosophical thought, about deconstruction and hospitality. The research methodology is exploratory-bibliographic, using books, articles, websites, magazines, contents and proceedings of Congresses.